Desorption of Coffee Pulp Used as an Adsorbent Material for Cr(III and VI) Ions in Synthetic Wastewater: A Preliminary Study - Dora Luz Gómez-Aguilar; Javier Andrés Esteban-Muñoz; Juan Pablo Rodríguez-Miranda; Deisy Baracaldo-Guzmán; Octavio José Salcedo-Parra (Molecules, 2022)
Some of the diverse agro-industrial waste generated in primary or secondary stages have proved to be promising biomaterials for treating aqueous effluents contaminated, in this case, with heavy metals. Therefore, it is necessary to know their optimal operating conditions and the regeneration or reusability of the solid by-product, an aspect related to desorption. Considering the above, this article presents the findings of a preliminary study related to the desorption process of coffee pulp without physicochemical modification (Castilla variety), an agricultural waste used as a sorbent of Cr(III and VI) ions in synthetic wastewater. The desorption efficiency of four eluting agents at defined concentrations (0.10M)—HC1, HNO3, H2SO4, and EDTA—was evaluated in a time interval of 1 to 9 days. Likewise, the proposals for the sorption and/or desorption mechanisms proposed and reported in the literature with respect to the use of biosorbents derived from the coffee crop are presented. With respect to the results, the coffee pulp used in previous studies of the adsorption of chromium species mentioned (optimal conditions in synthetic water of particle size 180 μm, dose 20 g·L−1, agitation 100 RPM, room temperature, time of 90 to 105 min) showed efficiencies in the removal of Cr(III) and Cr(VI) of 93.26% and 74.80%, respectively. Regarding the extracting substances used, H2SO4 0.10 M was the one that presented the highest desorption percentage in both chromic species, with a desorption of 45.75% Cr(VI) and 66.84% Cr(III) in periods of 5 and 9 days, respectively, with agitation of 100 RPM and room temperature. Finally, the dissemination of preliminary results on the desorption of coffee pulp contaminated with chromic species without physicochemical modification is novel in this study, as similar work with this specific material has not yet been reported in the literature. On the other hand, the limitations of the study and future research are related to the evaluation at different concentrations and of other extractor solutions that allow improving the efficiency of desorption of these chemical species in a shorter time from the coffee pulp (with and without modification) as well as the reuse cycles. As a result, the desorption of coffee pulp used as an adsorbent material in real water could help researchers identify the possible interfering factors that affect the process (foreign anions and cations, organic matter, environmental conditions, among others).